Microbial Community Diversity Dynamics in Acid Mine Drainage and Acid Mine Drainage-Polluted Soils: Implication on Mining Water Irrigation Agricultural Sustainability - Munyai, Rabelani; Ogola, Henry Joseph Oduor; Modise, David Mxolisi (Frontiers in Sustainable Food Systems, 2021)
Environmental degradation related to mining-generated acid mine drainage (AMD) is a major global concern, contaminating surface and groundwater sources, including agricultural land. In the last two decades, many developing countries are expanding agricultural productivity is in mine-impacted soils to meet food demand for the rapidly their growing population in The practise of AMD water (treated or untreated) irrigated agriculture is on the increase, particularly in water-stressed nations around the world. For sustainable agricultural production systems, optimal microbial diversity and functioning is critical for soil health and plant productivity. Thus, this review presents up-to-date knowledge on the microbial structure and functional dynamics of AMD habitats and AMD-impacted agricultural soils. The long-term effects AMD water such as soil acidification, HM, iron and sulfate pollution, greatly reduces microbial biomass, richness and diversity, impairing soil health plant growth and productivity and impacts food safety negatively. Despite the drawback on food safety and detrimental effect on soil health and agricultural productivity coupled with environmental degradation, AMD-impacted habitats are unique ecological niches for novel acidophilic, HM and sulfate-adapted microbial phylotypes that might be beneficial to optimal plant growth and productivity and bioremediation of polluted agricultural soils. This review has also highlighted the impact active and passive treatment technologies on AMD microbial diversity, further extending the discussion on the interrelated microbial diversity and beneficial functions such as metal bioremediation, acidity neutralization, symbiotic rhizomicrobiome assembly and plant growth promotion, sulfates/iron reduction and biogeochemical N and C recycling under AMD-impacted environment. The significance of SRB, FeOB, and PGPRs as key players in many passive and active systems dedicated to bioremediation and microbe-assisted phytoremediation is also elucidated and discussed. Finally, new perspectives on the need future studies, integrating meta-omics and process engineering on AMD-impacted microbiomes, key to designing and optimizing of robust active and passive bioremediation of AMD-water before application to agricultural production is proposed.